The parasites of ostriches - THEODOROPOULOS (Γ. ΘΕΟΔΩΡΟΠΟΥΛΟΣ), G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ostrich production is a new type of venture activity which has appeared in Greece recently. The objective of this paper is to present the parasites which have been found to parasitize ostriches and related species of birds, as well as to present an update of what we know today about their pathogenicity and measures of control.